2022
DOI: 10.1016/j.avsg.2021.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacies of Physical Examination in Patients with Acute Lower Limb Ischemia Are Associated with Dreadful Consequences

Abstract: Inadequacies of physical examination in patients with acute lower limb ischemia are associated with dreadful consequences,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
3
0
3
Order By: Relevance
“…Of major concern, though, was the report on the association between inadequate physical examination by the first doctor at the emergency department, resulting in delays in diagnosis and treatment, and lower amputation-free survival in this population. 17 Evaluation of primary conservative therapy in ALI, mainly with anticoagulation alone, has indeed been scarcely reported in the literature, particularly in adult patients, and only small case series are available. 18 The reasons for choosing primarily anticoagulation therapy in our study were often multiple as shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of major concern, though, was the report on the association between inadequate physical examination by the first doctor at the emergency department, resulting in delays in diagnosis and treatment, and lower amputation-free survival in this population. 17 Evaluation of primary conservative therapy in ALI, mainly with anticoagulation alone, has indeed been scarcely reported in the literature, particularly in adult patients, and only small case series are available. 18 The reasons for choosing primarily anticoagulation therapy in our study were often multiple as shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Of major concern, though, was the report on the association between inadequate physical examination by the first doctor at the emergency department, resulting in delays in diagnosis and treatment, and lower amputation-free survival in this population. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Il est rare que les 6 symptômes soient présents simultanément; la présentation la plus courante est la douleur au repos (71,3 %) 1 , 3 . Il est important de procéder à l’évaluation des 6 symptômes (6 P) et de l’indice de pression systolique (IPS) 4 ; la non-exécution d’un examen clinique adéquat incluant les 6 P et l’IPS est associée à une probabilité accrue d’amputation majeure et de décès 5 .…”
Section: La Douleur Aiguë à Un Membre Est Le Principal Symptôme Qui D...unclassified
“…Eine aktuelle Analyse aus Schweden unterstreicht die Wertigkeit dieser frühen klinischen Beurteilung auch im Zeitalter der rasch verfügbaren Bildgebung mittels Duplex-Ultraschall und CT-Angiografie. Mittels retrospektiver Analyse konnte gezeigt werden, dass in den 53 % der Patienten, bei denen initial eine zufriedenstellende Erfassung des Status des betroffenen Beins durchgeführt wurde, ein Vorteil im Hinblick auf die Reduktion der Mortalität und die Major-Amputationsrate erreicht werden konnte [4].…”
Section: Aktueller Stand Und Wahl Der Revaskularisationsstrategieunclassified